The Impact of IFRS on Value Relevance of Accounting Information: Evidence from the Indonesian Stock Exchange - Imanuel Wahyu Christanto; Fuad Fuad (University of Merdeka Malang, 2023)
This study investigates the relationships between several accounting variables, International Financial Reporting Standards (IFRS) adoption, and stock market prices in Indonesia. The variables of interest include lagged price, book value per share (BVPS), earnings per share (EPS), market capitalization, Revenue, and price-to-earnings (P/E) ratio. We apply multiple regression analysis to examine the influences of these factors on stock prices. Our preliminary findings suggest that EPS and BVPS have a significant positive association with market prices, aligning with existing literature and highlighting the importance of these measures for investors. Additionally, our results indicate that IFRS adoption improves the value relevance of accounting information in the Indonesian market. We also explore potential size-related variations in the impact of IFRS adoption on the value relevance of accounting information. This study contributes to the ongoing debate on the effectiveness of IFRS and provides insights to investors, policymakers, and practitioners about the factors influencing stock prices in Indonesia.